“Right to the truth” in the view of legal philosophy: foundation for the debate - Dobrzeniecki, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The text deals with the issue of “the right to the truth” in static and dynamic terms. The first one concerns the currently binding norms, the second — the law, whose characteristics are scarcely being shaped within the philosophy of law. In international law, the subject of the right is victims’ knowledge of past human rights violations. At the national level the legislator assumes that the disc-losure of information about the government’s activities is necessary for the effective functioning of democratic mechanisms. The author, based on the classical theory of truth created by Aristotle, tries to answer the question: is the liberal concept of “the marketplace of ideas” still an adequate mecha-nism for protecting this value, and if not, whether preserving the truth should become a function of public law. In some areas, public law already fulfils this function, and therefore the concept of “right to truth” ceases to be merely an expression of an idea or metaphor.
Keywords: right to the truth; freedom of speech; classical theory of truth; marketplace of ideas; public law